1999
DOI: 10.1021/ma981496w
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Enzymatic Cleavage of Diastereomeric Oligo(3-hydroxybutanoates) Containing Two to Eight HB Units. A Model for the Stereoselectivity of PHB Depolymerase from Alcaligenes faecalis T1

Abstract: So far, it is known that various poly(3-hydroxybutanoate), PHB, depolymerases are able to degrade all-(R) chains, cyclic (R) oligomers, oligolides, and polymers composed of rac-hydroxybutanoate, HB, but not all-(S) or syndiotactic (R,S) chains. We have now studied the ability for configurational recognition (stereoselectivity) by the purified PHB depolymerase from Alcaligenes faecalis T 1. To this end, a titristat/HPLC method has been developed for following the degradation of oligo(3-hydroxybutanoates), OHBs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 12 publications
4
48
0
1
Order By: Relevance
“…This result confirmed that the purified depolymerase has endo-hydrolase activity (see above, results with aPHB). Oligomers of (S)-3HB were not hydrolyzed at all and confirmed the specificity of the enzyme for the R isomers as it has been found for dPHB depolymerase of Alcaligenes faecalis (13).…”
Section: Products Of Enzymatic Nphb Hydrolysis-supporting
confidence: 82%
See 1 more Smart Citation
“…This result confirmed that the purified depolymerase has endo-hydrolase activity (see above, results with aPHB). Oligomers of (S)-3HB were not hydrolyzed at all and confirmed the specificity of the enzyme for the R isomers as it has been found for dPHB depolymerase of Alcaligenes faecalis (13).…”
Section: Products Of Enzymatic Nphb Hydrolysis-supporting
confidence: 82%
“…However, the enzyme hydrolyzed aPHB when this amorphous polymer was blended, or copolymerized, with a variety of crystalline polyesters (10 -12). Hydrolytic activity toward aPHB was clearly of an endo type because of the presence of S units along the chain, which are known not to be recognized by PHB depolymerases (10,13). The conclusion was drawn that in aPHB, efficient enzyme binding to the substrate is prevented by exceeding mobility of the polymer chains in the amorphous rubbery state.…”
mentioning
confidence: 97%
“…For determination of temperature stability, purified PhaZ1 (0.6 g) was incubated in assay buffer at 50°C for the times indicated before residual activity was determined (columns). 2 or MgCl 2 increased the activity to 130 or 140% at 1 mM, respectively, but decreased the activity at 5 mM (both to 75%) or at 10 mM (to 40 or 35%, respectively). EDTA partially inhibited PhaZ1, but a 5 mM concentration was necessary to obtain more than 50% inhibition.…”
Section: Resultsmentioning
confidence: 92%
“…Bachmann and Seebach proposed that PhaZ RpiT1 has four subsites (2, 1, -1, and -2) in its active site, in which three of the subsites must be occupied by 3HB units for cleavage to occur at the centre of the active site [106]. Homology modelling of PhaZ RpiT1 (the modelled residue range was from positions 124 to 294) based on the crystal structure of PhaZ Pfu suggested that Asn285 (color-coded according to molecular species) of PhaZ RpiT1 is located at the mouth of the crevice, immediately above His273, which probably involved subsite -1 (Figure 7 (A)).…”
Section: Proposed Active Site Model Of Phaz Rpit1mentioning
confidence: 99%